Integrating genome‐ and transcriptome‐wide association studies to uncover the host–microbiome interactions in bovine rumen methanogenesis - Wei Wang; Zhenyu Wei; Zhuohui Li; Jianrong Ren; Yanliang Song; Jingyi Xu; Anguo Liu; Xinmei Li; Manman Li; Huimei Fan; Liangliang Jin; Zhannur Niyazbekova; et al. (iMeta)
Abstract The ruminal microbiota generates biogenic methane in ruminants. However, the role of host genetics in modifying ruminal microbiota‐mediated methane emissions remains mysterious, which has severely hindered the emission control of this notorious greenhouse gas. Here, we uncover the host genetic basis of rumen microorganisms by genome‐ and transcriptome‐wide association studies with matched genome, rumen transcriptome, and microbiome data from a cohort of 574 Holstein cattle. Heritability estimation revealed that approximately 70% of microbial taxa had significant heritability, but only 43 genetic variants with significant association with 22 microbial taxa were identified through a genome‐wide association study (GWAS). In contrast, the transcriptome‐wide association study (TWAS) of rumen microbiota detected 28,260 significant gene–microbe associations, involving 210 taxa and 4652 unique genes. On average, host genetic factors explained approximately 28% of the microbial abundance variance, while rumen gene expression explained 43%. In addition, we highlighted that TWAS exhibits a strong advantage in detecting gene expression and phenotypic trait associations in direct effector organs. For methanogenic archaea, only one significant signal was detected by GWAS, whereas the TWAS obtained 1703 significant associated host genes. By combining multiple correlation analyses based on these host TWAS genes, rumen microbiota, and volatile fatty acids, we observed that substrate hydrogen metabolism is an essential factor linking host–microbe interactions in methanogenesis. Overall, these findings provide valuable guidelines for mitigating methane emissions through genetic regulation and microbial management strategies in ruminants.